PENGARUH JUMLAH FUNGSI KEANGGOTAAN PADA METODE FUZZY LOGIC TERHADAP HASIL PERAMALAN BEBAN LISTRIK JANGKA PANJANG - Renartha Kusuma, Sani; Sari Hartati, Rukmi; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2020)
Electric load in Sumbawa Besar Regency from 2011 - 2018 experienced an average increase of ± 6.6%. The electric load for the following year is not yet known, so forecasting is needed. Electric load forecasting has an important role in the energy management system. Many methods can be used for forecasting, one of them is the fuzzy logic method. Fuzzy logic method consists of 3 components, those are Fuzzification, Fuzzy Inference System, and Defuzzification. Fuzzification is an important component of the fuzzy logic method, so the proper configuration is needed in order to produce forecasting that is close to the actual data. The simulation was carried out in 3 conditions, those are the first conditions (3 membership functions), the second condition (5 membership functions), and the third condition (7 membership functions). The third condition obtained a MAPE value of 2,42%, while the second condition was 3,34%, and the first condition was 6,51%. The third condition obtained the simulation results in 2026 at 24,75MW, while the second condition was at 23,26 MW, and the first condition was at 20,97MW. The third condition is the best condition in this study, because it has the smallest MAPE value.